Designed to move? Physical activity lobbying and the politics of productivity. (January 2015) - Piggin, Joe
Objectives: Physical inactivity is a major public health concern. At a population level, it is increasingly perceived to be a social problem which is global and multidimensional, and which requires attention by a diverse range of state, private and civil society organisations. Given the increasing attention to physical in/activity by a range of interest groups, this paper explores the political dynamics that are present within physical activity promotion discourse. Specifically, the paper examines the political dynamics associated with a recent physical activity lobby document entitled Designed To Move (DTM). DTM was written and produced by a variety of corporate, government, and health promotion organisations. Method and analysis: This paper uses a critical policy framework to analyse the justifications for, and suggested techniques of, physical activity promotion. It examines the explicit and more subtle reasons used to justify physical activity recommendations, how causes of physical inactivity are conveyed, and who is identified as able to fix the problem. Conclusions: While DTM appears to be a positive and inspirational call to action, several aspects of the document are problematic. Significantly, older adults receive scant attention in the document, and are therefore removed from being potentially important agents in the proposed solution. DTM also frames the workplace milieu in a way that promotes 'productivity' and business 'fortune' above concern for and consideration of employees' material conditions of existence. The paper concludes by encouraging health researchers, physical activity students and health promoters to look behind and beyond assumptions about the causes of, and solutions to, physical inactivity.